EXPERIENCE THE THRILLING JOURNEY OF LYME CARDITIS - FROM HEART BLOCK TO RECOVERY! - Mingma Sherpa, DO (Elsevier, 2024)
Therapeutic Area: Pharmacologic Therapy Case Presentation: A 60-year-old gentleman with a history of sleep apnea visited the emergency department reporting lightheadedness and fainting. He had been experiencing physical discomfort, chills, and body aches for the past month. However, he lost consciousness at home which prompted his wife to take him to the hospital. In ED, he had a sinus bradycardia of 46 bpm and a new complete heart block seen on EKG. Despite receiving a single dose of 0.5 mg atropine, there was no improvement. All CBC and CMP results were within normal limits. He had recurrent torsades-de-pointe (TdP), which required three additional defibrillations of 200J. An echocardiogram showed left ventricular ejection fraction at 60%. His Lyme titer was positive for IgM and IgG antibodies. A dopamine drip was started to address prolonged 6-second pauses. After two days, the dopamine was gradually weaned off. He was treated with intravenous ceftriaxone until the atrioventricular block was resolved and the PR interval was less than 200ms. Once the QRS and PR interval improved with daily EKG monitoring, he was switched to oral doxycycline 100mg twice daily to complete the three-week course. On a follow-up EKG, he had a normal sinus rhythm of 60 bpm. He successfully completed an exercise stress test and had an appropriate chronotropic response without any new symptoms. Background: Lyme carditis is a rare ailment that can occur during disseminated Lyme disease. Symptoms include chest pain, palpitations, dizziness, shortness of breath, and, in severe cases, sudden cardiac death. It typically affects the AV node and causes QRS widening. The spirochete incites an inflammatory response, and Lyme disease is the most prevalent tick-borne illness in the US and Europe. Conclusions: In conclusion, Lyme carditis is a rare but serious condition that requires prompt recognition and treatment. The report highlights the importance of early diagnosis and treatment with antibiotics to prevent disease progression and mitigate cardiovascular complications. Admitting patients to a telemetry unit and monitoring their cardiac function is crucial in ensuring their safety. Patients with Lyme carditis can recover fully and resume their normal activities with appropriate treatment. Raising awareness about the disease and its potential complications is essential to prevent its spread and improve patient outcomes.